Объяснение:
{10-4(2х+5)=6у-13
{47-63=5(4х-2у)+2
10-8х-20=6у-13
-16=20х-10у+2
-8х-6у= - 13-10+20
-20х+10у=2+16
-8х-6у= - 3 |×5
-20х+10у=18 |×3
-40х-30у= - 15
-60х+30у=54
+ ——————
-100х=39
Х= - 0,39
10у=18+20х
10у=18+20×(-0,39)
10у=18-7,8
10у=10,2
У=1,02
ответ : (-0,39;1,02)
Объяснение:
{10-4(2х+5)=6у-13
{47-63=5(4х-2у)+2
10-8х-20=6у-13
-16=20х-10у+2
-8х-6у= - 13-10+20
-20х+10у=2+16
-8х-6у= - 3 |×5
-20х+10у=18 |×3
-40х-30у= - 15
-60х+30у=54
+ ——————
-100х=39
Х= - 0,39
10у=18+20х
10у=18+20×(-0,39)
10у=18-7,8
10у=10,2
У=1,02
ответ : (-0,39;1,02)